SMS Reference in National Library of Indonesia: Pilot Project Research - Wicaksono, Arief (Universitas Airlangga, 2016)
SMS looks outdated in todays digital era. Perhaps because of that, library did not chose SMS as media for reference services. Existing researchâs results prove different things with this assumption. Libraries in Indonesia itself seem do not use SMS as a medium in reference services. There is only the National Library of Indonesia (Perpusnas) which organized text reference services. This study sought understanding the conditions of text reference service at Perpusnas, including aspects of interpersonal communication. This research uses quantitative content analysis research on recorded text in text reference services. The results showed SMS has the potential to reach a wider market in the community for reference services. Text reference service at Perpusnas needs more planning, implementation, and evaluation which is found that sufficient length of the response time and the duration of the transaction. In addition, a reference librarian who runs the text reference service needs to pay attention to aspects of interpersonal communication which is a positive influence in the transaction reference.